2004
DOI: 10.1038/sj.sc.3101605
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative monitoring in scoliosis surgery with multi-pulse cortical stimuli and desflurane anesthesia

Abstract: This combination of anesthetic and stimulation protocols is efficacious for IOM during spinal cord surgery. Our findings support the use of desflurane for successful acquisition of MEPs during scoliois surgery as an alternative anesthetic regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
(15 reference statements)
2
17
4
Order By: Relevance
“…The results of this study are consistent with previous studies showing the relative equivalence of desflurane and propofol [8,9]. One difference in this study was the use of desflurane or propofol as the sole anesthetic agent without an adjunct anesthetic such as nitrous oxide.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are consistent with previous studies showing the relative equivalence of desflurane and propofol [8,9]. One difference in this study was the use of desflurane or propofol as the sole anesthetic agent without an adjunct anesthetic such as nitrous oxide.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of desflurane on MEPs, however, are limited. One group has reported MEPs with desflurane that are comparable to propofol [8,9]. Because of this limited information and especially since there is no data in the pediatric population, this retrospective study of the effect of desflurane on motorevoked potentials in children was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis confirmed results from studies in patients undergoing spinal surgery that indicated that tcMEPs are recordable independent of whether TIVA or inhalational agents were administered (Pechstein et al, 1998;Lo et al, 2004Lo et al, , 2006Hayashi et al, 2008Hayashi et al, , 2009. However, the primary goal of this study was to investigate the differences in tcMEP amplitudes depending on the choice of the anesthetic in CEA patients.…”
Section: Discussionsupporting
confidence: 72%
“…MEPs are more sensitive to the choice of anesthetic agents than SSEPs [24][25][26]. Anesthetic agents both inhaled and intravenous can depress SSEP and MEP with impairment of signal attainment.…”
Section: Discussionmentioning
confidence: 99%